A review of music performance anxiety in the lens of stress models - Twitchell, A. J.; Journault, A-A.; Singh, K. K.; Jamieson, J. P. (Frontiers in Psychology, 2025)
Music performance anxiety (MPA) is a widespread challenge among musicians, often impairing performance quality and well-being. While traditionally conceptualized as a debilitating condition, recent research suggests that MPA can have both facilitative and detrimental effects, depending on how it is appraised and regulated. This paper reviews theoretical stress models relevant to MPA, emphasizing frameworks such as stress optimization and synergistic mindsets that help reframe anxiety as a potential resource. By integrating insights from affective science and stress research, this review highlights the need for a more nuanced approach to MPA—one that moves beyond symptom reduction to foster adaptive responses that enhance musical performance. Future research should continue exploring personalized and flexible interventions that equip musicians with the tools to navigate evaluative pressure effectively.